The Cognitive Benefits of Arabic Debate: Implications for Vocabulary Acquisition - Mutmainah, Siti; Mahbub, Mahbub (AL-FIKRA, 2025)
Speaking and debating in Arabic has become an enjoyable approach for students to get better in the language, especially as the need to communicate with people worldwide increases. According to social data, many students still struggle with learning and using Arabic. Discussions encourage people to talk and think more critically, according to several research studies. However, fewer studies have examined their role in word learning. It is the first research to quantify the number and types of words people acquire through speech using a quasi-experimental approach. The aim of this research is This study examines whether arguments aid in vocabulary acquisition and enhance students critical thinking, speaking, and vocabulary.The purpose of this study is to find out how conversations affect students communication and critical thinking abilities as well as how effectively they support vocabulary learning. the impact of debate on students communication and critical thinking skills, as well as how effectively debate aids in word learning. We divided forty tenth graders at Satuan Muadalah Ulya into experimental and control groups. To assess their language development, we gave them tests both before and after ten weeks. According to the results, the debate method group learned much more vocabulary than the conventional method group. This study theoretically contributes to the corpus of information about the effectiveness of language learning strategies. These findings provide educators a fresh approach to becoming better in the actual world.